2019
DOI: 10.1088/1755-1315/388/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bioactive phytochemical compound of (Cyperus aucheri Jaub.) by using gas chromatography –mass spectrometry

Abstract: Twenty one bioactive phytochemical compound were identified in the methanolic extract of Cyperus aucheri Jaub. The identification of phytochemical compounds is based on the peak area, retention time, molecular weight and MS Fragmentation. GC-MS analysis of Cyperus aucheri Jaub. Revealed the existence of the 3-Phenylheptanoic acid, benzylammonium salt, 2-(benzyloxymethyl)-5-methylfuran, 4-methoxycarbonylphenyl)methyl 4-methylbenzoate, Benzoic acid, 4-methyl-,[4-(methoxycarbonyl)phenyl]methyl ester, dodeca-5,7-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Additional quantitative data were obtained by gas chromatography coupled to mass spectrometry (GC/MS). The experimental design was adapted from that used by Li and Fingas, while the analysis of the mass spectrum followed that reported for C14 by Abu-Serag et al and confirmed a molecular ion for C14 at 239.4 AMU …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional quantitative data were obtained by gas chromatography coupled to mass spectrometry (GC/MS). The experimental design was adapted from that used by Li and Fingas, while the analysis of the mass spectrum followed that reported for C14 by Abu-Serag et al and confirmed a molecular ion for C14 at 239.4 AMU …”
Section: Resultsmentioning
confidence: 99%
“…The experimental design was adapted from that used by Li and Fingas, 82 while the analysis of the mass spectrum followed that reported for C14 by Abu-Serag et al and confirmed a molecular ion for C14 at 239.4 AMU. 83 GC on control samples showed that C14 detection at low concentrations was at the instrumental limit of ∼1−5 mg/L or 1−5 ppm (Figure 9(Left)). The GC data for the octane extract after WG-1 immersion in PB for 1, 2, and 7 days at 37 °C are shown in Figure 9(Right).…”
Section: Antimicrobial Tests Minimum Inhibitory Concentration (Mic) A...mentioning
confidence: 99%
“…It is an essential oil found in medicinal plants Premna tomentosa (Priyadarshini et al 2017), in the leaves and fruits of Piper aduncum (Wibawa et al 2019), Artemesia lavandulaefolia (Yuan et al 2010), Cunninghamia lanceolata biomass (Qing-Zhia et al 2012), a bioactive phytochemical compound of Cyperus aucheri Jaub. (Abu-Serag et al 2019), and in Chinese ginger (Zingiber officinale Roscoe) rhizomes (Ding et al 2012;Choudhari and Kareppa 2013).…”
Section: Discussionmentioning
confidence: 99%
“…About 1μL of them ethanol extract was injected into the GC-MS column using a micro syringe and the scanning was done for 45minutes". [ 18,19]…”
Section: -Constituents Identification Of Extract By Gas Chromatograph...mentioning
confidence: 99%